Review On Car-License-Plate Detection Systems - Muravade, Supriya; Shete, Amruta; Takale, Priyanka; Chhajed, Gyankamal (International Journal of Computer Sciences and Engineering, 2015)
In this paper we have reviewed and analyzed different car-license-plate detection and recognition technique. We have reviewed different image processing Edge Detection techniques and recognition technique like Sobel operator, Canny operator, ANN, BPNN, Template matching. We have also represented analysis of these techniques in the form of table considering different factors of Edge Detection and recognition like visual quality, security, robustness and computational complexity. It is concluded that in edge detection techniques vertical edge detection technique are best with some factors like processing time, accuracy, while in recognition technique BPNN are best for some factors like execution speed or other image processing operations and security. The visual quality and computational complexity are common factors for both the technique.